Effect of the addition of honey on the growth of lactic acid bacteria in functional drinks of fermenting cassava stored at frozen temperatures. Issue 1 (April 2020) - Sari, N; Tahir, M M; Zainal,
Abstract: Cassava is a food that contains fat, protein, and minerals so that it can be processed by fermentation. The purpose of this study was to find out how to increase the content of honey against the growth of lactic acid bacteria associated with the probiotic tapai based cassava functional drinks stored in frozen storage conditions. Functional drinks based on cassava with additional honey 0%, 2%, 4%, 6%, and 8% which will then be analyzed by the total lactic acid bacteria. The results obtained indicate that the total lactic acid (LAB) bakery in cassava-based functional drinks ( Manihot esculenta ) in freezing temperature storage decreased in the treatment of honey additions of 2% and 4% but increased in the treatment of adding honey 6% and 8% despite the increase and decrease in total bacteria the results are not significantly different.